Cultural adaptation, the 3-month efficacy of visual art training on observational and diagnostic skills among nursing students, and satisfaction among students and staff- a mixed method study - Jia Guo; Qinyi Zhong; Ying Tang; Jiaxin Luo; Hongjuan Wang; Xiaofen Qin; Xiuhua Wang; James Allen Wiley (BMC, 2021)
Abstract Background Visual art training is a student-led approach using Western art pieces as the main teaching resources. It has been developed and applied in nursing and medical education in the United States. This study aimed to adapt visual art training to Chinese cultural context, then to compare the efficacy of the culturally-tailored visual art training versus traditional education on observational and diagnostic skills at 3-month follow-up among Chinese nursing students in master program. Methods This study included Phase 1 (cultural adaptation) and Phase 2 (3-month efficacy evaluation). It was conducted from June to September, 2019. In Phase 1, cultural barriers were identified and cultural adaptation strategy were made based on two focus group interviews. Phase 2 was a randomized controlled trial in a local museum. A total of 106 first-year nursing students in master program were randomized to the intervention group or the control group. Both groups received traditional education. In addition, intervention group received a visual art training (including a field-guided museum visit with observation and debriefing of Chinese oil paintings and clinical images, four teaching hours). Data were collected for both groups at baseline and 3-month follow-up on the observational and diagnostic skills measured by clinical image tests. Learning satisfaction with the visual art training was investigated among 53 intervention students and teaching satisfaction was done in 10 staff members by self-administered questionnaires. Results In phase 1, we adapted a culturally-tailored visual art training for nursing students in China. Observational skills of the intervention group increased significantly compared with the control group 3 months after the training (p < .001). A trend towards the improvement of diagnostic skills was indicated with increment of 2.92 points of the intervention group vs. 0.39 of the control group (p > .05). In general, all participants and staff were satisfied with the visual art training, especially the selected Chinese oil paintings and the student-led teaching process, but 34% (n = 18) were not satisfied with the long distance from the museum. Conclusions A culturally-tailored visual art training with great acceptability and feasibility was implemented in China. It had a sustained positive effect on improving the observational skills of Chinese nursing students. This study can be used for a reference to introduce visual art training to nursing students or nurses from other cultures. Trial registration Retrospectively registered in Chinese Clinical Trial Registry ( ChiCTR2000037956 ) on 4th September, 2020.